Mapping Agricultural Technology Innovation Research for Food Security: A Bibliometric Approach - Ahmad Suhaimi; Heldawati Heldawati; Ariyandi Ariyandi (Journal of Agribusiness and Natural Resources, 2025)
This study aims to map the development of agricultural technology innovation research in supporting food security using a bibliometric approach. The analysis was conducted on a dataset of scientific publications indexed in selected academic databases during the period 2015–2025, serving as the unit of analysis to identify conceptual structures, thematic clusters, research evolution, and emerging research gaps. The keyword visualisation results show the dominance of the themes of precision agriculture, artificial intelligence (AI), the Internet of Things (IoT), smart farming, and digital agriculture as the main drivers of the transformation of modern agricultural systems. The cluster map shows a close relationship between technological innovation, sustainability, and food security, while the density–centrality analysis places precision agriculture and digital agriculture as motor themes with high centrality and density. Thematic evolution shows a shift from the conservation and sustainability paradigm towards data-based and artificial intelligence-based agricultural systems integrated with digital governance and the circular economy. Although technology is the dominant focus, aspects of farmer adoption, governance, digital inclusion, and policy integration remain strategic research gaps. These findings confirm that the transformation of agriculture towards a resilient food system requires multidisciplinary integration between technological innovation, environmental sustainability, and institutional and public policy support.